2022
DOI: 10.1590/1516-3180.2021.0357.r1.30062021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 pandemic on colorectal cancer surgery

Abstract: BACKGROUND: The coronavirus disease-19 pandemic has changed the course of diseases that require emergency surgery. OBJECTIVE: To evaluate the effect of the COVID-19 pandemic on colorectal cancer disease stage. DESIGN AND SETTING: Retrospective analysis in the city of Rize, Turkey. METHODS: This was a comparative analysis on two groups of patients with various symptoms who underwent surgical colorectal cancer treatment. Group 1 comprised patients operated between March 11, 2019, and December 31, 2019; while gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…Most of the relevant studies available in the literature addressed the outcomes of the surgical treatment of colorectal cancer cases during the COVID-19 pandemic [ 1 17 18 19 20 ]. In comparison, this study addressed all colorectal cases, including those with malignant and benign pathologies and those who underwent elective and emergent admissions/operations during the prepandemic and pandemic periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the relevant studies available in the literature addressed the outcomes of the surgical treatment of colorectal cancer cases during the COVID-19 pandemic [ 1 17 18 19 20 ]. In comparison, this study addressed all colorectal cases, including those with malignant and benign pathologies and those who underwent elective and emergent admissions/operations during the prepandemic and pandemic periods.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological upstaging of colorectal cancer is another issue that has been speculated to be associated with delays in recognizing the symptoms of colorectal cancer, its diagnosis, and colorectal cancer surgery during the pandemic period [ 1 13 18 23 24 ]. In Uyan et al’s study [ 1 ], for instance, the authors found higher rates of emergency operations and more patients with N and M stages for colorectal cancer during the COVID-19 pandemic. They speculated that the increase in the number of advanced cancer cases was associated with the pandemic [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rostan et al demonstrated in their study that there is a linear relationship between the increase in tumour diameter in thyroid cancer, and mortality and recurrence 38 . In addition, in our study on colorectal cancers during the COVID-19 period, it was found that the tumour diameter, lymph node metastasis, and stage of the disease advanced with the delay in diagnosis 39 . In our study, it was found that the tumour diameter was significantly larger in Group 2.…”
Section: Discussionmentioning
confidence: 74%